Structural Changes in the Urinary Bladder of Streptozotocin-Induced Diabetic Rats and the Possible Protective Role of Insulin - Elnagar , Amir M. Bassam; Ibrahim, Suhaidah; Abouelnaga, Mostafa A. M.; Soliman , Amro Mohamed (IIUM Medical Journal Malaysia, 2018)
Introduction: Diabetes mellitus possesses severe adverse effects on the urinary bladder. Urinary bladder dysfunction is a common health problem affecting diabetic patients causing recurrent infections and urinary incontinence. Objective: To evaluate the histopathological changes in the tissue of urinary bladder in Streptozotocin (STZ) diabetic rats and the protective role of insulin. Methods: Thirty rats were classified into three groups: a control group which received no treatment (Group A), STZ diabetic group (Group B) and Insulin diabetic group (Group C). Animals were sacrificed after six weeks and urinary bladders were harvested and processed for light and electron microscopy. Results: Several histopathological changes were observed in the urinary bladder of the diabetic group including an increase in the thickness of the urothelium, epithelial cells with dark nuclei and large lenticular vesicles, and wide intercellular spaces with numerous collagen fibers. Treatment with insulin reduced the pathological changes induced by STZ. Conclusion: Diabetes mellitus caused significant pathological changes in the urinary bladder of experimental rats. For instance, treating diabetic animals with insulin prevented the development of damaging effects of diabetes on the urinary bladder.